Particle simulation on the Cell BE architecture - BOZ, BETÜL; TOPCUOĞLU, HALUK RAHMİ (SPRINGER, 2011)
This paper presents two parallel formulations for the Barnes-Hut algorithm on the Cell architecture, which differ in tree distribution and construction phases of the algorithm. In the initial parallelization, the domains are dynamically partitioned and assigned to the synergistic processing elements (SPEs), and SPEs construct local trees of the sub-domains in parallel. The enhanced parallelization scheme provides better clustering of the particles by sequentially constructing the global tree of the entire work space in the power processing element (PPE) and by partitioning the tree into sub-trees that can fit in the Local Store. SPEs operate on the sub-tree data and construct local trees in parallel. Our experimental evaluation indicates that this application performs much faster on the Cell BE compared to the Intel Xeon based system. Specifically, our first and second methods on the Cell BE outperform Intel Xeon by a factor of 5.8 and 7.1 for 8192 particles, respectively.
Keywords: N-body simulations; Barnes-Hut algorithm; Parallel algorithms; Cell BE architecture